Properties of asphaltic concrete AC14 containing coconut shell as coarse aggregate - Jeffry, Siti Nur Amiera (2015)
Nowadays, there are various researches that using waste materials as materials substitute. This is to produce a green and sustainable environment and at the same time to solve the main problem which is to reduce the waste materials. Pavement engineering is one of the fields that can contribute to solve this problem where the use of waste materials in pavement can be an alternative to reduce the waste materials, protect the environment, reduce the extraction of aggregates and at the same time to improve the quality of pavement. Various of researches have been done by using industrial and construction waste material as aggregates replacement in asphalt concrete. Recent studies have shown the successful of using agricultural waste material in concrete. However the use of agricultural waste in asphalt concrete has not been extensively studied. Hence, in this study the effects of coconut shell as coarse aggregate replacement in properties of asphaltic concrete AC14 was investigated. The aggregate properties tests, Marshall Mix design, resilient modulus, indirect tensile strength and dynamic creep test were examined. 5 mm size of coconut shell was used as coarse aggregates replacement at 10%, 20%, 30% and 40% The result shows that coconut shells modified samples had less stability compare to the control samples due to effects from the volumetric properties. Nevertheless, the sample contained 10% replacement of coconut shells showed higher resistance to deformation in comparison to control sample. It can be concluded that, 10% replacement of coconut shell in asphaltic concrete was suggested in modifying the samples.